Socio-economic profile of Sri Lankan repatriates in Kotagiri - Vedavalli, L. (Delhi : Konark Publishers, 1994)
Study relates to Kotagiri, Nilgiri District, Tamil Nadu.
Keywords: Kotagiri (India) -- Economic conditions; Kotagiri (India) -- Social conditions